Newspapers and politics in 2006 elections in Sarawak. - Stanley Bye Kadam-Kiai (Universiti Kebangsaan Malaysia, 2009)
Newspapers have tremendous impact on how people perceive their world and on how they make decisions. The political decisions the people make could be shaped a lot by what they read in the newspaper. Newspapers often have their own private agenda on what news they are going to communicate to the general public to attract their attention. In Malaysia, however, the newspapers must also know what the government wants them to publish; otherwise they risk their annual permits being revoked, terminated or suspended. As a consequence, mainstream newspapers in Malaysia in general give more coverage to the National Front or the Barisan Nasional (BN) which has governed the country since independence in 1957 and to its component parties especially the United Malay National Organisations (UMNO) and the Malaysian Chinese Association (MCA) at the national level, and the Parti Pesaka Bumiputera Bersatu (PBB) and the Sarawak United Peoples Party (SUPP) in the State of Sarawak than they do to the oppositions. The coverage is not only pro-BN, but it is so lopsided that the oppositions and many analysts alike often accused newspapers in the country guilty of extreme bias as they mainly cover news on the government and government related activities. Is this accusation accurate? Are newspapers in the country pro-government? One way to find out if this is so is to see how the two mainstream English newspapers in Sarawak, namely The Borneo Post and the Eastern Times, covered the Ninth Sarawak State Election which was held on 10-20 May 2006.